Serological diagnosis of soil-transmitted helminth (Ascaris, Trichuris and hookworm) infections: A scoping review. - Sara Roose; Fiona Vande Velde; Johnny Vlaminck; Peter Geldhof; Bruno Levecke (PLoS Neglected Tropical Diseases)
Background The World Health Organization emphasizes the importance of integrated monitoring and evaluation in neglected tropical disease (NTD) control programs. Serological assays offer a potential solution for integrated diagnosis of NTDs, particularly for those requiring mass drug administration (MDA) as primary control and elimination strategy. This scoping review aims (i) to provide an overview of assays using serum or plasma to detect infections with soil-transmitted helminths (STHs) in both humans and animals, (ii) to examine the methodologies used in this research field and (iii) to discuss advancements in serological diagnosis of STHs to guide prevention and control programs in veterinary and human medicine. Methodology We conducted a systematic search in the Ovid MEDLINE, Embase and Cochrane Library databases, supplemented by a Google search using predefined keywords to identify commercially available serological assays. Additionally, we performed a patent search through Espacenet. Principal findings We identified 85 relevant literature records spanning over 50 years, with a notable increased interest in serological assay development in recent years. Most of the research efforts concentrated on diagnosing Ascaris infections in both humans and pigs, primarily using ELISA and western blot technologies. Almost all records targeted antibodies as analytes, employing proteins and peptides as analyte detection agents. Approximately 60% of sample sets described pertained to human samples. No commercially available tests for Trichuris or hookworms were identified, while for Ascaris, there are at least seven different ELISAs on the market. Conclusions While a substantial number of assays are employed in epidemiological research, the current state of serological diagnosis for guiding STH prevention and control programs is limited. Only two assays designed for pigs are used to inform efficient deworming practices in pig populations. Regarding human diagnosis, none of the existing assays has undergone extensive large-scale validation or integration into routine diagnostics for MDA programs.